Testing Fama and French Three-Factor Model and Earnings-to-Price on Stock Excess Return - Ramdy, Zulmi (2011)
Bursa Efek Indonesia (BEI) is the centre of Indonesia equity market. This study empirically tests Fama and French three-factor model in Indonesia equity market characteristic which is influenced by Indonesia economic condition. Furthermore, new proposed model is also tested in this equity market where three-factor model is combined with earnings yield to explain variation on stock excess return. The result shows that stock excess returns is not affected by only market return but also by size and market to book ratio. Moreover, earnings yield helps three-factor model to capture more variation in stock excess return. The empirical results are consistent with Fama and French three-factor model and also four-factor model. In addition, involvement of earnings yield also is proved empirically improve efficiency of three-factor model.